CHILDREN WITH CHILDHOOD: SHAPING PERSONALITY IN DICKENS’ OLIVER TWIST AND BRONTË’S JANE EYRE - Nurul Imansari; Andi Mega Januarti Putri; Widia Pramesti (Univeristas Islam Negeri (UIN) Alauddin Makassar, 2021)
The study object in this research is childhood in Dickens’ Oliver Twist and Brontë’s Jane Eyre. Although the two novels were written by two different writers, however, the novels have similarities to some extent, particularly about the social issue in childhood. Being a symbol of growth and rebellion of the child in the novels, childhood conveys the relationship of the child’s survival and the shape of the character. Both Dickens’ and Brontë’s novel expresses some resemblances about childhood life. Through a critical analysis of Dickens’ and Brontë’s selected texts on the children characters, this research aims to compare and examine how the social status in childhood can create the individual personality and how the character changes in the novel throughout their childhood. Being a nineteenth century authors, Dickens and Brontë’s conform to the writing conventions of that period. The method used in this study was a descriptive qualitative. It will examine how the novel represents the characters by focusing on the various perspective of the narrator. The result shows that through the theme of childhood, both novels show the ability of this particular time of life to shape the personality of the character. The wicked condition in the institution, the absence of respect and affection, the ignorance of people, and the prejudice over the main character become the aspect in contributing the shape of Oliver and Jane’s personality. Both novels contain realism and drive the reader to become more aware and sympathetic towards the poor child.